2002
DOI: 10.1046/j.1365-2222.2002.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

Atopic sensitization among children in an Arctic environment

Abstract: Compared with European findings Greenlandic children have high levels of total IgE but a low prevalence of allergic sensitization towards inhalant allergens. This may be due to a low genetic susceptibility to atopy and less allergen exposure, as well as to living conditions in an arctic environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 29 publications
(23 reference statements)
4
32
0
Order By: Relevance
“…Higher sensitisation rates were observed when specific IgE levels were used for diagnosis. In younger children, sensitisation rates were between 4.2 % and 20.6 % (Julge et al, 2001), whereas in older children ranged between 0.4 % (Krause et al, 2002) and 22.7 % (Julge et al, 2001). In adults the figures were zero to egg yolk (Bakos et al, 2006) and 2.8 % to egg white.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Higher sensitisation rates were observed when specific IgE levels were used for diagnosis. In younger children, sensitisation rates were between 4.2 % and 20.6 % (Julge et al, 2001), whereas in older children ranged between 0.4 % (Krause et al, 2002) and 22.7 % (Julge et al, 2001). In adults the figures were zero to egg yolk (Bakos et al, 2006) and 2.8 % to egg white.…”
Section: Introductionmentioning
confidence: 90%
“…Rates of positive SPT in adults were between 6.4 % (Bakos et al, 2006) and 6.8 % (Schafer et al, 2001). For specific IgE levels, the only study from Norway in young children reported a prevalence of sensitisation of 3.4 % (Ro et al, 2012), whereas in older children the prevalence of sensitisation ranged between 2.6 % (Krause et al, 2002) and 12.2 % (Nicolaou et al, 2010). The latter study used a low cut-off point for determining sensitisation (0.2 kU/L), which may explain the higher sensitisation rates observed.…”
Section: Europementioning
confidence: 99%
“…To be categorised as Inuit ethnicity, both of the parents should be registered as born in Greenland. The applied approach to ethnicity has previously been validated in Greenlandic studies from our group [16]. Information on place of birth was obtained from the Danish Civil Registration System (CRS) that contains demographic information on all inhabitants of Greenland as well as Denmark [17].…”
Section: Study Site and Populationmentioning
confidence: 99%
“…Children whose parents were both born in Greenland were considered Inuit, as this method has been shown to accurately identify children of Inuit heritage. 18 By having parents or caretakers complete a standardized self-administered questionnaire, we also obtained information on crowding in the household (total number of dwellers, number of adults and number of children), parents' educational level, health status of the study child and type of heating in the household.…”
Section: Risk Factorsmentioning
confidence: 99%